Expression of HMB45, MelanA and SOX10 is rare in non-small cell lung cancer - Kriegsmann, Mark; Kriegsmann, Katharina; Harms, Alexander; Longuespée, Rémi; Zgorzelski, Christiane; Leichsenring, Jonas; Muley, Thomas; Winter, Hauke; Kazdal, Daniel; Goeppert, Benjamin; Warth, Arne (Diagnostic pathology, 2018)
Non-small cell lung cancer (NSCLC) and melanoma are frequent entities in routine diagnostics. Whereas the differential diagnosis is usually straight forward based on histomorphology, it can be challenging in poorly differentiated tumors as melanoma may mimic various histological patterns. Distinction of the two entities is of outmost importance as both are treated differently. HMB45 and MelanA are recommended immunohistological markers for melanoma in this scenario. SOX10 has been described as an additional marker for melanoma. However, comprehensive large-scale data about the expression of melanoma markers in NSCLC tumor tissue specimen are lacking so far.
Gesehen am 27.09.2018